2020
DOI: 10.1155/2020/4357194
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Complementary and Alternative Medicine among Saudi Older Adults: A Population‐Based Study

Abstract: Background. Complementary and alternative medicine (CAM) is an integral part of patients' therapeutic experience worldwide. Among Saudi older adults, less is known about CAM utilization. Objectives. To determine the prevalence, patterns, and factors associated with CAM utilization among SOA. Methods. In the Saudi National Survey for Elderly Health (SNSEH), subjects were asked about CAM use during the last twelve months before the interview. CAM use was defined as any use of herbal products, acupuncture, bloodl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 92 publications
0
10
1
1
Order By: Relevance
“…Several researchers from a national multistage survey data have observed that despite the extent and density of healthcare facilities and the free healthcare system within the country, Saudis’ abstain from seeking advice unless disease symptoms worsen or have reached advanced stages of illness [ 24 , 25 ]. Furthermore, there is a high prevalence of the use of complementary and alternative medicine among the Saudi population ranging between 65 and 80% [ 26 ], and musculoskeletal symptoms were the most reported reasons for use [ 27 ]. It is also possible that workers believe that their musculoskeletal symptoms are related to stress, rather than actual physical causes.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers from a national multistage survey data have observed that despite the extent and density of healthcare facilities and the free healthcare system within the country, Saudis’ abstain from seeking advice unless disease symptoms worsen or have reached advanced stages of illness [ 24 , 25 ]. Furthermore, there is a high prevalence of the use of complementary and alternative medicine among the Saudi population ranging between 65 and 80% [ 26 ], and musculoskeletal symptoms were the most reported reasons for use [ 27 ]. It is also possible that workers believe that their musculoskeletal symptoms are related to stress, rather than actual physical causes.…”
Section: Discussionmentioning
confidence: 99%
“…62 The same pattern was also observed during COVID-19 pandemic, where patients reported using herbal products and acupuncture to alleviate their symptoms. 63 , 64 Another parallel between Ebola and COVID-19 is the fact that there was a lack of solid evidence-based treatments at the initial phase of the epidemic, 62 which resulted in the search for non-pharmacological therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the holistic nursing approach should include religion and spiritual interventions, since pain, negative experiences such as mental stress are frequently present in medical problems [6] and other studies use of CAM in Saudi older adults using multivariable Cox regression showed that the death hazard ratio in 2006 and 2015 showed no difference in mortality between groups of CAM users and nonusers [7]. Many previous studies have examined descriptively [2,4,7,8] while the analysis regarding the time to improve complementary therapy is still limited. Some of the factors that are suspected to be the affected improvement of mental health condition is gender.…”
Section: Introductionmentioning
confidence: 99%